The effect of applying the snowball throwing method on learning outcomes of Islamic religious education UMI literature faculty student - Nurjannah Nurjannah (Jurnal Scientia, 2024)
The research problem is how the learning process of PAI before and after using the snowball throwing method for students of the Faculty of Letters of UMI and whether the snowball throwing method is effective and communicative. One of the alternative, effective and communicative learning methods is the Snowball Throwing method. The research problem, how is the PAI learning process before and after using the snowball throwing method for students of the Faculty of Letters UMI and whether the snowball throwing learning method can improve the PAI learning outcomes of students of the Faculty of Letters UMI. The purpose of the study was to describe the learning process of Islamic Education before and after using the snowball throwing method and to describe the effectiveness of the snowball throwing learning method in improving the learning outcomes of Islamic Education for students of the Faculty of Letters of UMI. This research is a class action research with research subjects of UMI Faculty of Letters students. Data collection techniques through tests, observations, interviews and documentation. Data were processed with descriptive analysis. The results showed that Islamic Religious Education learning, generally lecturers use the lecture method which tends to produce less effective and boring learning activities, while the application of the snowball throwing method in Islamic Religious Education learning is very effective, because it encourages active students and emphasizes all students to be ready and focused on receiving material and answering questions from the questions given, emphasizes teamwork and has implications for the value of student final results indicated by changes in knowledge, understanding, speaking skills, awakened cooperation between students during the teaching and learning process.